DEVELOPMENT OF ARTIFICIAL INTELLIGENCE PLATFORMS THAT SUPPORT DATA-DRIVEN DECISION MAKING FOR BUSINESSES AND IMPROVE ECONOMIC PRODUCTIVITY - Aastha Shah; Liaquat Ali Khan (Antis Publisher, 2025)
Objective: This study explores the development and implementation of AI platforms that facilitate intelligent business decision-making and enhance economic productivity. Method: Through a mixed-methods approach combining case study analysis and quantitative performance evaluation, we examine how AI-powered analytics platforms transform raw data into actionable business insights. Results: Our findings indicate that organizations implementing AI decision support systems experience an average 28% improvement in operational efficiency and 19% increase in revenue growth. Novelty: The research provides a framework for successful AI platform adoption and identifies critical success factors for maximizing economic returns.